Factors Influencing Knowledge and Motivation of Health Cadres in Preventing Stunting in Children in Karo Regency - Tampubolon, Nathania Septhia (International Journal on Health and Medical Sciences, 2024)
: Stunting remains a significant public health issue in many regions, particularly in rural areas like Karo Regency, Indonesia. This study aimed to explore the factors influencing the knowledge and motivation of health cadres in preventing stunting among children. Using a mixed-methods approach, data were collected through surveys and interviews with health cadres, local health officials, and community leaders. The research identified critical gaps in the knowledge of health cadres regarding stunting prevention strategies, emphasizing the need for more localized, frequent, and tailored training programs. Additionally, the study found that health cadres were motivated by both intrinsic factors, such as personal commitment to the community, and extrinsic factors, including financial incentives and institutional support. The involvement of local community leaders in stunting prevention initiatives emerged as a crucial factor for success. However, barriers such as limited resources, financial constraints, and logistical challenges were found to hinder the effectiveness of these efforts. The findings suggest that addressing these gaps in knowledge, improving training and support systems, and fostering community collaboration are essential to enhancing stunting prevention programs in Karo Regency. The research contributes to a deeper understanding of the factors influencing health cadres' effectiveness in stunting prevention and offers recommendations for improving public health strategies in the region.